Controllable Fabrication of Sub-10 nm Graphene Nanopores via Helium Ion Microscopy and DNA Detection - Yuan, Zhishan; Lin, Yanbang; Hu, Jieming; Wang, Chengyong (Biosensors (Basel), 2024)
Solid-state nanopores have become a prominent tool in the field of single-molecule detection. Conventional solid-state nanopores are thick, which affects the spatial resolution of the detection results. Graphene is the thinnest 2D material and has the highest spatial detection resolution. In this study, a graphene membrane chip was fabricated by combining a MEMS process with a 2D material wet transfer process. Raman spectroscopy was used to assess the quality of graphene after the transfer. The mechanism behind the influence of the processing dose and residence time of the helium ion beam on the processed pore size was investigated. Subsequently, graphene nanopores with diameters less than 10 nm were fabricated via helium ion microscopy. DNA was detected using a 5.8 nm graphene nanopore chip, and the appearance of double-peak signals on the surface of 20 mer DNA was successfully detected. These results serve as a valuable reference for nanopore fabrication using 2D material for DNA analysis.